2011
DOI: 10.3402/ijch.v70i4.17836
|View full text |Cite
|
Sign up to set email alerts
|

Traditional food and monetary access to market-food: correlates of food insecurity among Inuit preschoolers

Abstract: Objectives. To evaluate correlates of food insecurity among Inuit preschoolers. Study design. Cross-sectional health survey. Methods. Correlates of food insecurity were assessed in 3-5 year old children (n=388) residing in 16 Nunavut communities (2007)(2008) in whom a high prevalence of child food insecurity (56%) has been documented. A bilingual team conducted interviews, including 24-hour dietary recalls and past-year food security assessment involving monetary access to market foods. Results. Children resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 28 publications
3
50
0
Order By: Relevance
“…Others have noted the high cost of food and pervasive rates of poverty commonly experienced by communities in the Canadian Arctic as determinants of diet quality and food insecurity (16,31,32). Inuit are highly vulnerable to food insecurity as a result of geographic location; high levels of under-employment and unemployment; and low income, all of which affect the purchase of perishable, healthy food from local stores and limit the purchase of equipment needed to maintain traditional activities (2,3,7,31,32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have noted the high cost of food and pervasive rates of poverty commonly experienced by communities in the Canadian Arctic as determinants of diet quality and food insecurity (16,31,32). Inuit are highly vulnerable to food insecurity as a result of geographic location; high levels of under-employment and unemployment; and low income, all of which affect the purchase of perishable, healthy food from local stores and limit the purchase of equipment needed to maintain traditional activities (2,3,7,31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Dependence on informal, traditional social support networks may play an important role in filling the gap between a household's economic constraints and its accessibility to country food. Country foods are rich in nutrients, contribute to higher dietary quality, promote good health and provide a sense of wellness that comes from the participation in cultural activities (16)(17)(18)31,33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across the globe, various processes of environmental dispossession have had the effect of limiting or reducing access to traditional foods among Indigenous populations, leading to the gradual replacement of these foods with marketed or pre-manufactured products. This transition has had dramatic consequences for dietary quality and cultural identity, along with the health and maintenance of TFS (Cidro, Adekunle, Peters, & Martens, 2015;Egeland, Williamson-Bathory, Johnson-Down, & Sobol, 2011;Johnson-Down & Egeland, 2010). In Canada, only about a quarter of First Nation adults consume wild meat from their local environments and even fewer (18.6%) include wild plants and berries as part of their diets (FNIGC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The transition away from traditional food has consequences for diet quality, nutrient intakes and nutritional status (10)(11)(12). For example, we found that on days when traditional food was consumed 22.7% of energy came from protein and 37.2% of energy came from carbohydrates as opposed to 13.9% of energy from protein and 50.8% of energy from carbohydrate when no traditional food was consumed (10).…”
Section: Special Editorialmentioning
confidence: 78%